Role of vitamin D3 combined to alginates in preventing acid and oxidative injury in cultured gastric epithelial cells. Issue 1 (December 2016) - Uberti, Francesca; Bardelli, Claudio; Morsanuto, Vera; Ghirlanda, Sabrina; Molinari, Claudio
Abstract Background Gastric diseases are a worldwide problem in modern society, as reported in the USA, in the range of 0.5–2 episodes/year/person and an incidence of 5–100 episodes/1000/week according to seasons and age. There is convincing evidence that oxidative stress is involved in the pathogenesis of acute gastric injury. Acid secreted from gastric parietal cells determines mucosal injuries which in turn cause inflammation and oxidative stress. Consequent inflammation produces free radicals by mitochondria thus causing lipid peroxidation, oxidative and acidic stress, which can lead to cell apoptosis. Vitamin D3, the active form of vitamin D, may counteract intracellular cell death and improve epithelial regeneration. Methods This study was planned to assess whether vitamin D3 is a protective factor against acid injury and oxidative stress in gastric epithelial cells. Primary epithelial cells and GTL-16 cells have been used to test the effects of Grisù® alone or in combination with vitamin D3 during oxidative stress or high acid exposition measuring cell viability, ROS production, cellular adhesion time along with apoptotic, autophagic and survival pathways. The combined effect of Grisù® and vitamin D3 was found more effective in counteracting the negative consequences of oxidative stress and acidity conditions than some other gastroprotective agents, such as Maalox® or Gaviscon®. Results In case of oxidative stress or acidity condition the stimulation with Grisù® alone caused an improvement of cell viability and a reduction of ROS production on epithelial gastric cells. In addition, the adhesion time of the cells was improved. All these effects were increased by the presence of vitamin D3 . Similar data were also observed in primary gastric epithelial cells confirming the results obtained in GTL-16 cells. Conclusions These results suggest that Grisù® in combination with vitamin D3 may exert a gastroprotective effect to maintain or restore the integrity of gastric epithelium through an antioxidant pathway, inhibiting apoptosis and activating survival kinases. Moreover, the combination of Grisù® and vitamin D3 improves cell viability and decreases ROS production compared to other gastroprotective agents combined with vitamin D3 . All these data were validated using primary cells isolated from gastric tissue.